(untitled) (Theatrum historiae, 2024)
In this article, the author examines the political writings of French authors in the 18th century concerning plans to repair the Polish-Lithuanian Commonwealth. The scale of this phenomenon was aboveaverage, thanks to the activity of the Bar Confederation deputy Michał Wielhorski, at whose instigation leading representatives of the French Enlightenment from different political and ideological camps joined the discourse. The author makes a comparison between the solutions that were presented and tries to show the similarities related to Michal Wielhorski’s interference in the texts of their treatises and the differences resulting from the ideological divergence between their authors. Furthermore, he presents excerpts from the texts that suggest the influence of the founder of the texts on their final shape. An attempt is also made to assess to what extent the plans that were presented were a real attempt to help the Commonwealth and to what extent they were rather personal political-ideological manifestos of the individual authors.